(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2023)
The purpose of this study is to determine the specific effects of job stress and job insecurity on millennial employees’ desire to quit their employment. This study is categorized as verification and descriptive research since it employs a quantitative methodology. The tool consists of a set of inquiries dispersed via Google Forms. The questionnaire employed in this study has a strongly agree to strongly disagree range so that respondents can select and give direct answers. An SLR, or systematic literature review, is used in this process. 25 studies were found using the keywords "namely individual characteristics, work stress, job insecurity and turnover intention" in a database that was sourced from Google Scholar publications. These articles were then assessed for this study. Application of studies on how work-related stress, employment instability, and personal traits affect the intention to quit. This body of research will demonstrate a variety of factors that affect turnover intentions. The results of this study show that personal traits, stress, and job insecurity—findings that are corroborated by several academic studies—have a favorable impact on the intention to quit.